Technical Guidance on Broiler Chicken Maintenance Management in Livestock Businesses in Puosu Jaya Village, Konda District - Hafid, Harapin; Ananda, Siti Hadrayanti; Ibrahim, Anita Mustika (Journal of Saintech Transfer, 2021)
The activity aims to provide Technical Guidance on Broiler Chicken Maintenance Management for Breeders in Puosu Jaya Village, Konda District. The problem experienced was the low knowledge of the farming community about how to manage chickens so that they can increase their productivity. Community service activities are carried out by implementing a chicken intensification technology package so that it was more profitable and develops in the community, especially the breeder community. The method of activity was carried out in preliminary activities, counseling and demonstrations as well as evaluation design. It can be concluded that the community really needs guidance in developing the potential of broiler farms that they have been working on, which has an impact on increasing income and developing chicken population.